Vendor‐neutral sequences and fully transparent workflows improve inter‐vendor reproducibility of quantitative MRI. Issue 3 (3rd June 2022) - Karakuzu, Agah; Biswas, Labonny; Cohen‐Adad, Julien; Stikov, Nikola
Abstract : Purpose: We developed an end‐to‐end workflow that starts with a vendor‐neutral acquisition and tested the hypothesis that vendor‐neutral sequences decrease inter‐vendor variability of T1, magnetization transfer ratio (MTR), and magnetization transfer saturation‐index (MTsat) measurements. Methods: We developed and deployed a vendor‐neutral 3D spoiled gradient‐echo (SPGR) sequence on three clinical scanners by two MRI vendors. We then acquired T1 maps on the ISMRM‐NIST system phantom, as well as T1, MTR, and MTsat maps in three healthy participants. We performed hierarchical shift function analysis in vivo to characterize the differences between scanners when the vendor‐neutral sequence is used instead of commercial vendor implementations. Inter‐vendor deviations were compared for statistical significance to test the hypothesis. Results: In the phantom, the vendor‐neutral sequence reduced inter‐vendor differences from 8% to 19.4% to 0.2% to 5% with an overall accuracy improvement, reducing ground truth T1 deviations from 7% to 11% to 0.2% to 4%. In vivo, we found that the variability between vendors is significantly reduced ( p = 0.015) for all maps (T1, MTR, and MTsat) using the vendor‐neutral sequence. Conclusion: We conclude that vendor‐neutral workflows are feasible and compatible with clinical MRI scanners. The significant reduction of inter‐vendor variability using vendor‐neutral sequences has important implications for qMRI research and for the reliability of multicenter clinical trials.